Forest carbon sink in North China increased in recent two decades, but decreased in extreme drought years - Xinran Huang; Zhen Zhen; Wenxin Zhao; Xiaochun Wang (GIScience & Remote Sensing, 2024)
North China is one of China’s most severely warming and drying regions, and understanding the dynamics of forest carbon sinks in North China is critical for forest management in response to climate change. This study examined the spatial and temporal dynamics of forest carbon sinks in North China from 2000 to 2020 using carbon cycle process and soil respiration data, and explored the relationship between the sinks’ spatial and temporal dynamics and changes in major climatic factors, particularly the effects of droughts on the forest sinks. The results showed that forest net ecosystem productivity (NEP) in North China increased significantly at 7.0 gC·m−2·yr−1 over the last 21 years, mainly concentrated along Yanshan (e.g. Hebei Province) and Qinling (e.g. south-central Shaanxi Province) area. Shaanxi had the fastest NEP growth rate, while Henan had the slowest. The spatial distribution of forest NEP in North China decreased with increasing latitude, and the increase in NEP from 2000 to 2010 attained 115 gC·m−2 was higher than that from 2010 to 2020. Moisture is the main climatic factor affecting forest carbon sinks in North China, but there is some spatial heterogeneity in the response patterns to precipitation, drought, and temperature in different regions. Drought levels have dramatically impacted forests in North China, and drought losses and post-drought recovery for NEP increased as drought levels increased. Extreme drought had the greatest impact on the forest NEP, with a loss of up to 93.46 gC m−2, but the recovery from drought was much greater than the loss from drought, the entire increase might be as high as 120 gC·m−2. Forest carbon sinks in North China have superior drought resistance, recovery, and resilience. This study illustrates the impact of conservation measures like afforestation in North China through the dynamic distribution of carbon sinks and also highlights the impacts of drought events with varying severity on forest carbon sinks.